Mobility Tool Use Relates to Disability Affirmation among Adults with Visual Impairments. (September 2021) - Zapata, Mercedes A.
Introduction: Research is beginning to support the association between positive disability identity and well-being among individuals with disabilities, including those with visual impairments (i.e., blindness and low vision). To enhance practitioner understanding of how to support individuals with visual impairments, research is needed to examine how disability identity attitudes may vary based on disability characteristics in this population.Methods: Using multiple linear regression, the author examined the association between impairment-related factors and personal disability identity (PDI; i.e., disability affirmation and disability acceptance) and group disability identity (GDI) in a sample of 212 adult U.S. residents with visual impairments.Results: Results of this study indicated that participants who use a mobility tool (cane, dog guide, or both) have higher self-reported disability affirmation ( p = .001)—an identity construct related to feelings of disability pride versus shame—after controlling for age, gender, and impairment-related factors (e.g., severity indicators). The Cohen's f 2 value for the affirmation model was .15, a medium effect size (Cohen, 1988). The regression on GDI indicated that younger participants, in general, reported higher feelings of connection to the disability community (i.e., higher GDI; p = .001); Cohen's f 2 was .13, a small effect. The regression on disability acceptance yielded non-significant findings.Discussion: Researchers and practitioners working with adults who have visual impairments should consider the relationship between an individual's disability affirmation and decision-making regarding mobility tool use and training . Future research should also examine hypotheses regarding the negative association between age and GDI among adults with visual impairments.Implications for practitioners: Practitioners within the field of visual impairment may benefit from a consideration of consumer disability identity, including disability affirmation and disability group affiliation.